Effectiveness of The Educational Game “Engklek” In Prevention of Dengue Hemorrhagic Fever - Deska Viorentira; Marleni Marleni; Ayudita Ayudita (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito, which can be prevented by implementing the PSN 3M Plus principle, namely draining, covering, recycling, and taking additional measures. This study aims to evaluate the effectiveness of the educational game "Engklek" in improving children's knowledge, attitudes, and self-confidence towards DHF prevention. The method used is mixed methods with quantitative and qualitative approaches. The quantitative design uses a quasi-experimental design with two groups pretest posttest, while the qualitative design involves in-depth interviews. The sample consisted of 80 students of grades IV and V, divided into intervention and control groups. Quantitative data analysis was carried out using the Paired t-Test and independent t-test. The results showed a significant increase in knowledge scores (p = 0.000), attitudes (p = 0.004), and self-confidence (p = 0.045) after the intervention. The conclusion of this study is that the “Engklek” game is effective as an educational medium for dengue fever prevention, and it is recommended to be widely implemented in schools as part of interactive health promotion.